Uji Aktivitas Antibakteri Ekstrak Daun Suruhan (Peperomia Pellucida (L.) Kunth) Terhadap Bakteri Staphyloccocus Epidermidis - Fardani, Roushandy; Apriliani, Rabulani (JSN : Jurnal Sains Natural, 2023)
Staphylococcus epidermidis is a gram-positive bacterium that can cause skin infections, one of which is acne. Acne (acne vulgaris) is a chronic inflammatory disease of the pilosebaseus unit characterized by the presence of blackheads, papules, pustules, nodules, cysts, and scars. Acne often occurs on the skin of the face, neck, chest and back. Although acne is not fatal, it is quite troubling because it can reduce self-confidence, especially those who care about appearance. The purpose of this study was to identify the antibacterial activity of suruhan leaf extract (Peperomia pellucida (L.) kunth) against Staphyloccocus epidermidis bacteria. The research method with well diffusion is to see the presence of clear zones formed around wells that show the inhibition of the growth of Staphyloccocus epidermidis bacteria by Peperomia pellucida (L.) kunth leaf extract. The object of study was the extract of uruhan leaves and bacteria Staphyloccocus epidermidis. Data were obtained using primary data from observation or direct observation of the area of inhibition zone of uruhan leaf extract against Staphyloccocus epidermidis bacteria. From the results of the study showed that there was an inhibitory power of the leaf extract against Staphyloccocus epidermidis bacteria.